Wildfire A Reader - True Aliannor (American : Island Press, 2001)
This collection gathers a wide variety of stories and essays written on wildfire in America. The editor, who contributes a piece describing a summer she spent fighting fires on the North Rim of the Grand Canyon, has included works ranging from Native creation myths to modern stories of wildfire up to the 2000 Cerro Grande fire near Los Alamos, NM. Also covered are selections from writers as diverse as Edward Abbey, John Muir, Mark Twain, Aldo Leopold, John McPhee, and others. True has attempted to show how our attitude toward wildfire has changed from adversarial to accepting. For instance, today we use controlled burns to restore open spaces and clear underbrush choking many forests owing to years of aggressive fire suppression. Recommended for all natural science collections, this unique collection should especially appeal to public library patrons. [This title joins a recent boomlet of new books about wildfires, including David Strohmaier's The Seasons of Fire: Reflections on Fire in the West (LJ 6/15/01), Stephen Pyne's Year of the Fires: The Story of the Great Fires of 1910 (LJ 5/15/01), and Sebastian Junger's forthcoming Fire (Norton, October). Ed.] Tim Markus, Evergreen State Coll. Lib., Olympia, WA.
- Tim Markus, Evergreen State Coll. Lib., Olympia, WA.
Copyright 2001 Reed Business Information, Inc.
Keywords: Sinh thái cháy